Isochronal recovery behaviour on electromagnetic properties of polycrystalline nickel zinc ferrite (Ni0.5Zn0.5Fe2O4) prepared via mechanical alloying - Nor Hapishah, Abdullah; Muhammad Syazwan, Mustaffa; Mohd Nizar, Hamidon; Farah Nabilah, Shafiee; Ismayadi, Ismail; Idza Riati, Ibrahim (Springer Nature Limited, 2021)
A new approach through heat treatment has been attempted by establishing defects by the process of quenching towards electrical and magnetic properties in the nickel zinc ferrite (Ni0.5Zn0.5Fe2O4) sample. The measured property values in permeability and hysteresis characteristic gave their recovery behaviour in which the values, after quenching were recovered after undergoing the annealing. Interestingly, a diferent trend observed in the permittivity value whereas the value was increased after quenching and subsequently recovered after annealing. The mechanisms which produced the changes is believed to be involved by defects in the form of vacancies, interstitials, microcracks and dislocations created during quenching which gave rise to changes in the values of the complex permeability and permittivity components and hysteresis behaviour.